Reintegrating Kadazandusun Identity Fragmentation through Sabah Indigenous Filmmaking - Sydney Thomas, Sibangan (Natural Volatiles & Essential Oils, 2025)
This study examines the role of Kadazandusun telemovies in fostering cultural cohesion, resisting assimilation, preserving indigenous identity within Malaysia’s broader multicultural framework. The Kadazandusun community, with its 45 sub-ethnic groups, has historically struggled to consolidate a unified identity due to socio-political, linguistic, and cultural fragmentation. Compounded by Malaysia’s dominant Malay-centric narrative, these challenges necessitate alternative avenues for cultural preservation. This research addresses the limited academic focus on Kadazandusun filmmaking, proposing that these telemovies serve as both artistic expressions and strategic tools for unification. By applying the Indigenous Film Analysis Framework, this study evaluates the works of prominent Kadazandusun filmmakers—Tony Francis Gitom, Ramli Ahmad, Alfred Ujin, and Marc Abbas—analysing themes of contest/negotiation, perseverance, and self-definition. Using Benedict Anderson’s Imagined Community and Barry Barclay’s Fourth Cinema theoretical frameworks, it explores how these films construct an imagined Kadazandusun identity and assert cultural sovereignty. The research objectives are: (1) to evaluate the thematic content of selected telemovies through the Indigenous Film Analysis Framework, (2) to explore the representation of Kadazandusun identity within the Imagined Community, and (3) to assess the role of filmmaking in preserving storytelling authority through Fourth Cinema. Findings reveal that Kadazandusun telemovies reinforce collective identity, facilitate intra-community dialogue, and safeguard cultural memory amidst modernisation. This research contributes to indigenous media studies by highlighting cinema’s potential in sustaining and strengthening Kadazandusun identity.